Essential functional molecules associated with SARS-CoV-2 infection: Poten‐ tial therapeutic targets for COVID-19 (2020)
The whole world is still suffering substantially from the coronavirus disease 2019 (COVID19) outbreak. Several protein-based molecules that are associated with the Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which are essential for its functionality, survival, and pathogenesis have been identified and are considered as potential therapeutic targets. These protein-based molecules are either structural/non-structural components of SARS-CoV-2 or host factors, which play a crucial role in this infection. Developing drug molecules against these essential functional molecules to hinder their regular functioning and associated physiological pathways could be promising for successful clinical management of this novel coronavirus infection. The review aims to highlight the functional molecules that play crucial roles in SARS-CoV-2 pathogenesis. We have emphasized how these potential druggable targets could be beneficial in tackling the COVID-19 crisis.